Acute effects of static and dynamic stretching on hamstrings` response times - Ayala, F.; de Ste Croix, M.; Sainz de Baranda, P.; Santonja, F. (Journal of Sports Sciences, 2014)
The main purposes of this study were to (a) investigate acute effects of static and dynamic lower limb stretching routines on total response time, pre-motor time and motor time of the medial and lateral hamstrings during maximal eccentric isokinetic knee flexion; and (b) determine whether static and dynamic routines elicit similar responses. A total of 38 active adults completed the following intervention protocols in a randomised order on separate days: (a) non-stretching (control condition), (b) static stretching and (c) dynamic stretching. After the stretching or control intervention, total response time, pre-motor time and motor time of the medial and lateral hamstrings were assessed during eccentric knee flexion movements with participants prone. Measures were compared via a mixed-design factorial ANOVA. There were no main effects for total response time, pre-motor time and motor time. The results suggest that dynamic and static stretching has no influence on hamstrings response times (total response time, pre-motor time and motor time) and hence neither form of stretching reduces this primary risk factor for anterior cruciate ligament injury.